2018
DOI: 10.1016/j.toxicon.2018.11.207
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin for the treatment of hand tremor

Abstract: The aim of this study is to review our longitudinal experience with onabotulinumtoxinA (onaBoNT-A) injections for medically refractory hand tremor. We performed a retrospective review of our database of patients treated with onaBoNT-A for hand tremor evaluated between 2010 and 2018 in at least 2 sessions with follow-up. The majority were injected into the forearm flexors (FF), although treatment was individualized. During the specified period, 91 patients (53 essential tremor, 31 dystonic tremor, 6 Parkinson's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…BoNT has been investigated as a treatment option for essential hand tremor since the early 1990s 55–60. Several open-label trials have shown that BoNT decreases the tremor amplitude; the improvement is predominantly of the postural component of the tremor 57 59–61. However, there are certain limitations to treatment of limb tremor with BoNT.…”
Section: Bont Therapy For Limb Tremormentioning
confidence: 99%
“…BoNT has been investigated as a treatment option for essential hand tremor since the early 1990s 55–60. Several open-label trials have shown that BoNT decreases the tremor amplitude; the improvement is predominantly of the postural component of the tremor 57 59–61. However, there are certain limitations to treatment of limb tremor with BoNT.…”
Section: Bont Therapy For Limb Tremormentioning
confidence: 99%
“…However, these techniques do not aid to objectively determine BoNT treatment patterns. 11 Techniques such as muscle palpation, EMG measurement of muscle tremor, or multi-joint kinematic tremor analysis are required to identify tremulous muscles for determining injection patterns. 10 , 12 Currently there are no standardized assessment methods for the selection of muscle groups to be targeted by BoNT-A for determining tremor treatment pattern without producing excessive arm weakness.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few case studies and open-label studies on BoNT in dystonic tremor. One of the largest case studies is from Baylor University in 31 patients with dystonic head tremor [23]. The mean dose of BoNT (OnabotulinumtoxinA) was 77.3 units with a range of (27.5-187.5) units.…”
Section: Botulinum Toxin In Dystonic Hand Tremormentioning
confidence: 99%